The Adaptation of Small Intestine Nitregic Myenteric Neurons on Rats (Rattus norvegicus) to High Fat Diet - Amelia Hana; Sarmin Sarmin; Claude Mona Airin; Christin Marganingsih Santosa; Pudji Astuti (Buletin Peternakan, 2019)
High fat diet can result in the loss of nitrergic neurons in the myenteric plexus. The study aimed at finding out the effect of high fat diet on the adaptation of nitrergic nerve of rat intestine. It used 15 male rats (Rattus norvegicus) of a month of age with mean body weight of 53.73 gr. The rats were adapted for 7 days to individual cages with ad libitum feeding. After random adaptation, all of the rats were assigned to 3 groups of five rats, namely K-7, K-10, and K-13 groups. Feed and drinking water were given ad libitum. The treatment of the high fat diet lasted for 7 weeks. After the treatment, all of the rats were fasted for 12 hours and then killed. Subsequently, small intestine segments (duodenum, jejunum, and ileum) were taken. The intestinal segments were prepared by using NADPH-d histopathological technique to determine the morphometric changes of nitrergic myenteric neurons. During the treatment the rats were weighed every week and at the end of the study orbitalis vein blood measurement was carried out to see its glucose, cholesterol and cholecystokinin (CCK) plasma levels. The data of body weight, glucose, cholesterol, CCK levels, the total number of the nippergenic myenteric segments of the small intestine were statistically analyzed using Anova. The results of the study showed that the treatment of 7% to 13% fat diets for 7 weeks did not indicate any weight gain and any increase in cholescystokinin level, and any decrease in glucose level. However, it indicated significant increase in cholesterol level. The treatment of 10% and13% fat diets increased the total number of neurons in the jejunum and the ileum. Thus, it was concluded that the treatments of the high-fat diet of the rats (K-7, K-10, and K-13) for 7 weeks had significant effect on the adaptation of the neurons of the jejunum and the ileum.